Developing Inquiry-Based Worksheet to Explore The Mathematics Critical Thinking for Seventh Grader Students - Rully Charitas Indra Prahmana; Teguh Wibowo; Arie Purwa Kusuma; Ageng Triyono (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
This study aims to develop student worksheets with a guided inquiry approach that meet valid and practical criteria. The type of research is research and development (RD). The development model used is a 4D model consisting of define, design, development, and disseminate stages. This study involved material validators, media validators, and 7th grade students of Al Azhar 26 Islamic Junior High School Yogyakarta. The research data was obtained from the results of the assessment using a validation sheet and student response questionnaires. The average score of the assessment results from the material validators is 74 with very good validity level criteria, from media validators 127.5 with very good validity level criteria, and from the large group practicality test an average of 88 with very good practicality criteria. Student worksheets are declared valid and practical based on the stages of development and established criteria, and can then be used to explore students' critical thinking skills.